7 - Changing the Culture of Migration? Attitudes towards Education among Former Basotho Labour Migrants to South African Mines - Maphosa, France; Morojele, R. N. (Africa Development, 2021)
Until late in the 1990s, employment for unskilled and uneducated able-bodied Basotho men on South African mines was usually available. As a result, the education of male children in most Basotho households was not prioritised. In the 1990s, massive retrenchments took place at the mines, resulting in many Basotho men being retrenched and repatriated. Most of those retrenched did not have any formal education and were generally unskilled. Many of the ex- miners believed that they were retrenched to make way for an educated workforce. Back home, they experienced problems getting employment because of their lack of formal education. These experiences, combined with efforts by the government of Lesotho and its development partners to promote education, have led to a change in the attitudes of the former miners towards education. Most of them now have positive attitudes towards education as they perceive it as a more secure and more sustainable means of getting employment and a vehicle for economic and social mobility. Based on qualitative data obtained from former mine workers this paper provides evidence that as a result of new realities, former migrants are developing positive attitudes towards education. The change in attitude towards education can however, only evolve into a change in the culture of migration if, over time, the benefits of education outweigh those of migration.